(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The purpose of this study is to see if religious discipline has a substantial impact on the emotional intelligence of Grade VIII students at Madrasah Tsanawiyah Darul Aufa Sungai Buluh. The research method employed in this study is quantitative, with a sample size of 49 persons. Different sampling procedures are used to determine the sample to be utilized in research; in this study, researchers used a probability sampling strategy, namely the cluster sampling technique (area sampling). Based on the study’s findings that worship discipline has a substantial effect on student’s emotional intelligence, students who practice worship discipline have high emotional intelligence. According to the findings of inferential statistical analysis employing path analysis, the total influence of worship discipline on emotional intelligence was 99.5%.